Method for preparing leather pallets in tannery by using tanning chrome-containing leather ash
By bonding the chrome-containing leather ash in the leather and adding modified materials to form a high-strength and flexible pallet, the problem of difficult chrome-containing leather ash is solved, and cost reduction and performance improvement are achieved.
Patent Information
- Application Number
- CN202310230763.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-08
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-03-08
AI Technical Summary
The chromium-containing leather ash produced by tannery is difficult to effectively utilize, resulting in waste of resources and high production costs. The products prepared by existing methods are small in consumption, high in cost and difficult to promote.
By bonding the chrome-containing leather ash in the leather, and adding a layer of modified glue, toughener, softener and polyethylene during the bonding process, a tray with high strength and flexibility is formed.
The pallet can withstand 2 tons of pressure and maintain flexibility and water resistance during long-term use, reducing production costs, and excellent product performance and easy to promote.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the utilization of chrome-containing leather ash, and in particular to a method for preparing a pallet for carrying leather in a tannery by utilizing the chrome-containing leather ash. Background Art
[0002] The total amount of leather waste in the world is about 5 million tons, of which leather dust is a type of protein solid waste containing chromium, synthetic grease, oil, tanning agent and dye generated in the leather production process. Every ton of leather processed generates about 2kg to 6kg of leather dust solid waste.
[0003] Chinese patent 2018102125052 provides a method for preparing functional micronized leather ash synthetic leather powder, comprising the following steps: (1) pretreatment of ground leather ash; (2) preparation of hyperbranched polymer modified leather ash; (3) blending with a negative ion releaser to prepare functional micronized leather ash. The synthetic leather wet coating powder prepared by this method enables the synthetic leather to have negative ion release, endogenous formaldehyde capture, and excellent hygienic properties. Its main disadvantage is that the preparation cost is too high and it is difficult to apply industrially.
[0004] Characterization of asphalt binder for flexible pavement modified with leather buffing ash (C.Kamaraj1, Thabiba SM.F2, SivaSankari P2, et al. Characterization of asphalt binder for flexible pavement modified with leather buffing ash, China Leather, 2018, 47(1): 35-41) was published, using chromium-containing BD (buffing ash) to make useful products, thereby reducing pollution to the environment. A new asphalt binder was developed by mixing VG-30 asphalt binder, styrene-butadiene-styrene block copolymer (SBS), warm mix additive (Sasobit) and BD in the laboratory. Super pavement asphalt binder test, rotational viscometer and dynamic shear rheometer (DSR) were used to test performance grade (PG). The test procedure followed the standard ASTM D 6373, and the new asphalt binder was named PG-88. The physical and chemical properties such as FT-IR, DSC / TGA, SEM / EDAX, rheological properties and aging were evaluated. From the DSR value, PG 88 has better anti-fatigue (G*.sinδ) and anti-rutting (G* / sinδ) performance, and it can be used as an alternative asphalt glue for asphalt pavement. Its main disadvantage is that due to market capacity restrictions, the amount of leather ash used is too small, and it cannot be used as the main choice for waste resource utilization.
[0005] The Chinese invention patent ZL 2019108571085 authorized by this team provides a method for making particle board using chrome-containing grinding leather ash, wherein the treated chrome-containing grinding leather ash, glue, nitrogen-phosphorus flame retardant, toughening agent, toughening synergist, flame retardant synthetic fatliquor, substance B and water-based transparent waterproofing agent are mixed evenly, put into a mold, heated and pressurized in a flat vulcanizer, and sprayed with substance C and isopropyl palmitate on the surface, and the particle board is obtained after curing. The obtained particle board has good flame retardancy, wear resistance and dye stability. The present invention uses a physical-chemical combination of leather scraps as particle board without destroying the material of leather ash, but the surface of the particle board is not smooth and the surface is easy to fall off due to friction for a long time, which is easy to be restricted in promotion.
[0006] In summary, the solid chromium-containing wastes produced by leather making are mainly chromium-containing leather shavings and chromium-containing leather ash. After chemical hydrolysis, the chromium-containing leather shavings are mainly used as protein powder, cement foaming agent, liquid fertilizer, gelatin, etc., while the chromium-containing leather ash contains dyes of different colors, so it is difficult to use it for the same purpose as chromium-containing leather shavings. The main reason is that there are a large number of dyes, which need to be decolorized and the processing cost is extremely uneconomical. The current uses have the defects of small dosage, high cost, and difficulty in promotion.
[0007] Pallets are frequently used tools in the storage and transportation of raw leather. Each tannery needs to use a large number of pallets every year. The pallets used by the tanneries in the sales process of leather products are difficult to return to the tannery. Therefore, a large number of pallets are needed every year, which increases a lot of costs. Chrome-containing leather ash is currently difficult to use. Therefore, using chrome-containing leather ash as pallets is a good way to reduce the production costs of enterprises. Summary of the invention
[0008] The present invention utilizes chrome-containing leather ash from leather making to bond, thereby solving the disadvantages of low bonding strength due to the fluffy dyed leather ash during the bonding process. After bonding, the leather ash can withstand a tare weight of 2 tons. At the same time, due to the decrease in moisture content of the leather ash in the tray, the tray is prone to hardening and the pressure resistance decreases. A softener is used to adjust the hardness so that the hardness has a certain degree of softness, thereby enhancing the flexibility and enabling the tray to withstand a tare weight pressure of more than 2 tons during long-term use (the traditional idea is that the leather ash is exposed for a long time and is prone to lose moisture, resulting in a decrease in bearing capacity). At the same time, in order to enhance the waterproofness of the leather ash, a polyethylene layer (170-190° C.) is extruded around the tray to make the tray surface smooth, thereby protecting the original hide, leather blank and leather products and preventing them from being scratched.
[0009] A method for preparing a pallet for carrying hides in a tannery from chrome-containing leather ash, characterized in that:
[0010] (1) 10 kg of dried chrome-containing ground leather ash, 1.5-2.5 kg of special modified rubber, 0.3-0.5 kg of toughening agent, 0.04-0.08 kg of toughening synergist, 0.2-0.4 kg of synthetic fatliquor for pallets, and 0.1-0.2 kg of softener are mixed evenly, placed at room temperature for 30 minutes, put into a 40-50 mm mold, the pressure of the flat plate vulcanizer is 10-12 MPa, the temperature is 110-120° C., heated and pressurized in the flat plate vulcanizer, the processing time is 30-80 minutes, and then 10-20 g of isopropyl palmitate is sprayed on the surface of the leather ash extrudate, and the pallet carrier is obtained after curing;
[0011] (2) 5 kg of PE particles are placed in a twin-screw extruder to obtain master batches, and then the modified master batches are placed in a casting device to prepare a modified film. The twin-screw extruder and the casting device both have multiple heating zones, zone 1 is 160°C; zone 2 is 170°C; zone 3 is 165°C, the extruder speed is 40 r / min, and the casting speed is 70 r / min. The PE particles are sprayed onto the tray carrier obtained in step (1). The spraying speed is controlled so that the thickness of pE around the tray carrier is 2.0-2.5 cm. The film is left to stand for 1 hour to obtain a tray with a skin.
[0012] The toughening agent is any one of nitrile rubber, polyvinyl butyral and polyvinyl acetate;
[0013] The toughening synergist is any one of sodium p-vinylbenzene sulfonate (sodium p-styrene sulfonate), cycloisopropyl malonate and 3,4-dimethylaniline;
[0014] The preparation method of the special modified rubber is as follows: 50g of versatate vinyl carbonate, 60g of vinyl acetate, 1.1-1.4g of polyvinyl alcohol and 120g of deionized water are added into a flask, and the polyvinyl alcohol is fully dissolved at 70-80°C; 1.2-1.4g of ammonium persulfate is added, and the dropping speed is adjusted, and the dropping time is 2h. After the dropping is completed, the temperature is kept at 70-80°C for 1h, and 4-6g of butyl acrylate, 3-6g of hydroxyethyl acrylate, 1-2g of ammonium persulfate, 1-2g of triethoxyvinylsilane and 0.5-1.5g of 2-ethoxyethylamine are added, and the mixture is stirred and reacted at 80°C for 1-2h, and 0.8-2.2g of N-phenylurea is added, and the mixture is reacted at 40-50°C for 30min, cooled to room temperature, and discharged to obtain the modified rubber;
[0015] The preparation method of the special synthetic fatliquor for pallets is as follows: 21 g of tetradecanol is added into a flask, heated to 70-80° C., and the water therein is removed by vacuuming, and then 9.8-11 g of maleic anhydride and 1.6-2.2 g of anhydrous sodium acetate are added under stirring, and the mixture is reacted at 80-95° C., and then 9.6-10.6 g of diethanolamine and 6.2-7.5 g of 2,2-dihydroxymethylpropionic acid are added, and the mixture is heated to 90-130° C., and 3.2-4.8 g of pentadecylsulfonyl chloride is added at the same temperature, and the mixture is reacted for 1 h, and then 12.5 g of anhydrous sodium sulfite is added, and the mixture is stirred and reacted at 70° C. for 1 h, and finally 45-55 g of water is added, and the mixture is reacted at 80° C. for 2 h, and the obtained product is the special synthetic fatliquor for pallets.
[0016] The preparation method of the softener is as follows: 10.3g of soluble starch and 100-200g of deionized water are added to a reaction bottle, the dissolved soluble starch is put into a water bath, nitrogen protection is used, the temperature is maintained at 10-20°C, 3.8-5.3g of sodium periodate is added evenly three times, oxidation is carried out in the dark for 12-24h, 10.9g of barium chloride is added, stirring is carried out for 30min, suction filtration is carried out to obtain a colorless transparent liquid, 7.8g of oxalic acid is added, the reaction is carried out at 70°C for 1h, 93-95g of castor oil is added to the system, the reaction is carried out at 65-75°C for 1-2h, 40.3-51.3g of ethylene glycol is added, the reaction is carried out at 60-75°C for 1h, 9.8-10.2g of concentrated sulfuric acid is added dropwise under stirring for 1h, the reaction is carried out by heat preservation for 1-2h, the concentrated sulfuric acid is washed out with 60mL of saturated sodium chloride solution, the pH is adjusted to 6-7, and the softener is obtained.
[0017] The advantages of the present invention are:
[0018] (1) White latex has poor water resistance and cold resistance. When used in leather ash bonding, it is easy to cause the leather ash to fall off after contact with water during subsequent use, and the material is easy to harden in cold weather. The α-C of tertiary esters used in the present invention has abundant alkyl groups, which has great steric hindrance and shielding effects, protecting itself and the surrounding groups. Therefore, when copolymerized with vinyl acetate, tertiary esters can protect the ester groups of adjacent vinyl acetate, thereby reducing the hydrolysis rate of the ester groups and improving the stability, weather resistance and water resistance of the polymer. In addition, due to the presence of alkyl groups, the molecular polarity of versatate vinyl carbonate is very small, so it has strong hydrophobicity and good reactivity. Butyl acrylate and hydroxyethyl acrylate are used to increase the softness of white latex to increase its flexibility in a hardened environment and to improve the cold resistance of white latex. However, after the addition of butyl acrylate and hydroxyethyl acrylate, the gel on the stirring rod and the wall of the three-necked flask increases sharply. Triethoxyvinylsilane and 2-ethoxyethylamine are used, and the synergistic effect principle of coupling and 2-ethoxyethylamine on the solution gel dispersion is adopted to reduce the gel of the modified white latex. At the same time, N-phenyl urea is used to increase the rigidity and toughness of the white latex, so that the glue can meet the requirements of pallet use.
[0019] (2) The present invention uses tetradecanol to carry out a ring-opening reaction with maleic anhydride in a weakly alkaline environment, and the alcohol group reacts with the acid anhydride to generate a carboxylic acid and an ester group with a double bond. The resulting product is then reacted with diethanolamine and 2,2-dihydroxymethylpropionic acid to obtain an intermediate product with a hydroxyl group at the end group, and then dodecylsulfonic acid chloride with a flexible chain segment is added, wherein the sulfonic acid chloride reacts with the hydroxyl group to introduce a dodecyl chain segment with a flexible chain segment into the fatting agent. At the same time, in order to increase the hydrophilicity of the fatting agent, sodium sulfite is used to reduce the double bond, and a sodium sulfonate group is introduced into the double bond, thereby enhancing the hydrophilicity of the fatting agent. The resulting fatting agent has flexibility, and the imino group and hydroxyl group in the fatting agent increase the affinity of the fatting agent with leather scraps.
[0020] (3) The softener synthesized by the present invention has the dual effects of anti-wrinkle and softening. The soluble starch used is oxidized under sodium periodate conditions to generate a compound with a dialdehyde group. The compound can cross-link with the amino group in leather ash to prevent the leather scraps from extending during the extrusion process. At the same time, the present invention introduces castor oil, whose hydroxyl group can combine with the carboxyl group of oxalic acid. At the same time, the remaining carboxyl group in oxalic acid combines with the hydroxyl group in the soluble starch. The resulting product is sulfated under the action of concentrated sulfuric acid. In order to prevent the aldehyde group from being oxidized, ethylene glycol is used for protection. The unreacted concentrated sulfuric acid is washed off with saturated sodium chloride, and the pH is adjusted to allow the aldehyde group to react reversibly to obtain a softener with the dual effects of anti-wrinkle and softening.
[0021] (4) The chromium-containing leather ash from tanning is used for bonding to solve the problem of low bonding strength caused by the fluffy dyed leather ash during the bonding process. After bonding, it can withstand a pressure of 2 tons of leather. At the same time, due to the decrease in moisture content of the leather ash in the pallet, the pallet is prone to hardening and the pressure resistance decreases. Softener is used to adjust its hardness so that it has a certain degree of softness in the hardness, thereby enhancing its flexibility and enabling the pallet to withstand a pressure of more than 2 tons of leather during long-term use (the traditional idea is that the leather ash is exposed for a long time and is prone to lose moisture, resulting in a decrease in bearing capacity). At the same time, in order to enhance the waterproofness of the leather ash, a polyethylene layer (170-190°C) is extruded around the pallet to make the surface of the pallet smooth, protect the original hide, leather blank and leather products, and avoid them from being scratched.
[0022] The chrome-containing leather ash of the present invention comes from the leather used after adjusting the dyed leather blanks of Zibo Dahuan Jiubaoen Leather Co., Ltd. The dyed leather blanks of the same blank have basically similar colors, and the PE can be high-density polyethylene or timidium polyethylene. DETAILED DESCRIPTION
[0023] Example 1
[0024] A method for preparing a pallet for carrying hides in a tannery from chrome-containing leather ash, characterized in that:
[0025] (1) 10 kg of dried chrome-containing ground leather ash, 1.5 kg of special modified rubber, 0.3 kg of nitrile rubber, 0.04 kg of sodium vinylbenzene sulfonate, 0.2 kg of synthetic fatliquor for pallets, and 0.1 kg of softener were mixed evenly, placed at room temperature for 30 minutes, put into a 40 mm mold, the pressure of the flat plate vulcanizer was 102 MPa, the temperature was 110 ° C, heated and pressurized in the flat plate vulcanizer, and the processing time was 30 minutes. Then, 10 g of isopropyl palmitate was sprayed on the surface of the leather ash extrudate, and the pallet carrier was obtained after curing;
[0026] (2) 5 kg of PE particles are placed in a twin-screw extruder to obtain master batches, and then the modified master batches are placed in a casting device to prepare a modified film. The twin-screw extruder and the casting device both have heating zones, zone 1 is 160° C.; zone 2 is 170° C. (zones 1 and 2 of the twin-screw extruder, the same below); zone 3 is 165° C. (casting device, the same below), the extruder speed is 40 r / min, and the casting speed is 70 r / min. The PE is sprayed onto the tray carrier obtained in step (1), and the spraying speed is controlled so that the thickness of the PE around the tray carrier is 2.0-2.5 cm. The tray is left to stand for 1 hour to obtain a tray with a skin.
[0027] The preparation method of the special modified rubber is as follows: 50g of versatate vinyl carbonate, 60g of vinyl acetate, 1.1g of polyvinyl alcohol and 120g of deionized water are added into a flask, and the polyvinyl alcohol is fully dissolved at 70°C; then 1.2g of ammonium persulfate (dissolved in 50ml of water) is added, the dropping speed is adjusted, the dropping time is 2h, and after the dropping is completed, the temperature is kept at 70°C for 1h, and then 4g of butyl acrylate, 3g of hydroxyethyl acrylate, 1g of ammonium persulfate (dissolved in 50ml of water), 1g of triethoxyvinylsilane and 0.5g of 2-ethoxyethylamine are added, and the mixture is stirred and reacted at 80°C for 1h, and then 0.8g of N-phenylurea is added, and the mixture is reacted at 40°C for 30min, cooled to room temperature, and discharged to obtain the modified rubber;
[0028] The preparation method of the special synthetic fatliquor for pallets is as follows: 21 g of tetradecanol is added into a flask, heated to 70°C, and the water therein is removed by vacuuming, and then 9.8 g of maleic anhydride and 1.6 g of anhydrous sodium acetate are added under stirring, and the mixture is reacted at 80°C, and then 9.6 g of diethanolamine and 6.2 g of 2,2-dihydroxymethylpropionic acid are added, and the mixture is heated to 90°C, and 3.2 g of pentadecylsulfonyl chloride is added at the same temperature, and the mixture is reacted for 1 hour, and then 12.5 g of anhydrous sodium sulfite is added, and the mixture is stirred at 70°C for 1 hour, and finally 45 g of water is added, and the mixture is reacted at 80°C for 2 hours. The obtained product is the special synthetic fatliquor for pallets.
[0029] The preparation method of the softener is as follows: 10.3g of soluble starch and 100g of deionized water are added to a reaction bottle, the dissolved soluble starch is put into a water bath, nitrogen protection is used, the temperature is maintained at 10°C, 3.8g of sodium periodate is added evenly three times, oxidation is carried out in the dark for 12h, 10.9g of barium chloride is added, stirring is carried out for 30min, suction filtration is carried out to obtain a colorless transparent liquid, 7.8g of oxalic acid is added, the reaction is carried out at 70°C for 1h, 93g of castor oil is added to the system, the reaction is carried out at 65°C for 1h, 40.3g of ethylene glycol is added, the reaction is carried out at 60°C for 1h, 9.8g of concentrated sulfuric acid is added dropwise under stirring for 1h, the reaction is carried out at the temperature for 1h, the concentrated sulfuric acid is washed out with 60mL of saturated sodium chloride solution, the pH is adjusted to 6-7, and the softener is obtained.
[0030] Example 2
[0031] A method for preparing a pallet for carrying hides in a tannery from chrome-containing leather ash, characterized in that:
[0032] (1) 10 kg of dried chrome-containing ground leather ash, 2.5 kg of special modified rubber, 0.5 kg of polyvinyl butyral, 0.08 kg of cycloisopropyl malonic acid, 0.4 kg of synthetic fatliquor for pallets, and 0.2 kg of softener were mixed evenly, placed at room temperature for 30 minutes, put into a 50 mm mold, the pressure of the flat plate vulcanizer was 12 MPa, the temperature was 120 ° C, heated and pressurized in the flat plate vulcanizer, and the processing time was 80 minutes. Then, 20 g of isopropyl palmitate was sprayed on the surface of the leather ash extrudate, and the pallet carrier was obtained after curing;
[0033] (2) 5 kg of PE particles are placed in a twin-screw extruder to obtain master batches, and then the modified master batches are placed in a casting device to prepare a modified film. The twin-screw extruder and the casting device both have heating zones, zone 1 is 160°C; zone 2 is 170°C; zone 3 is 165°C, the extruder speed is 40 r / min, and the casting speed is 70 r / min. The PE particles are sprayed onto the tray carrier obtained in step (1). The spraying speed is controlled so that the thickness of pE around the tray carrier is 2.0-2.5 cm. The tray carrier is left to stand for 1 hour to obtain a tray with a skin.
[0034] The preparation method of the special modified rubber is as follows: 50g of versatate vinyl carbonate, 60g of vinyl acetate, 1.4g of polyvinyl alcohol and 120g of deionized water are added into a flask, and the polyvinyl alcohol is fully dissolved at 80°C; then 1.4g of ammonium persulfate (dissolved in 50ml of water) is added, the dropping speed is adjusted, the dropping time is 2h, and after the dropping is completed, the temperature is kept at 80°C for 1h, and then 6g of butyl acrylate, 6g of hydroxyethyl acrylate, 2g of ammonium persulfate (dissolved in 50ml of water), 2g of triethoxyvinylsilane and 1.5g of 2-ethoxyethylamine are added, and the mixture is stirred and reacted at 80°C for 2h, and then 2.2g of N-phenylurea is added, and the mixture is reacted at 50°C for 30min, cooled to room temperature, and discharged to obtain the modified rubber;
[0035] The preparation method of the special synthetic fatliquor for pallets is as follows: 21 g of tetradecanol is added into a flask, heated to 80°C, and the water therein is removed by vacuuming, and then 11 g of maleic anhydride and 2.2 g of anhydrous sodium acetate are added under stirring, and the mixture is reacted at 95°C, and then 10.6 g of diethanolamine and 7.5 g of 2,2-dihydroxymethylpropionic acid are added, and the mixture is heated to 130°C, and 4.8 g of pentadecylsulfonyl chloride is added at the same temperature, and the mixture is reacted for 1 hour, and then 12.5 g of anhydrous sodium sulfite is added, and the mixture is stirred at 70°C for 1 hour, and finally 55 g of water is added, and the mixture is reacted at 80°C for 2 hours. The obtained product is the special synthetic fatliquor for pallets.
[0036] The preparation method of the softener is as follows: 10.3g of soluble starch and 200g of deionized water are added to a reaction bottle, the dissolved soluble starch is put into a water bath, nitrogen protection is maintained at a temperature of 20°C, 5.3g of sodium periodate is added evenly three times, oxidation is carried out in the dark for 24h, 10.9g of barium chloride is added, stirring is carried out for 30min, suction filtration is carried out to obtain a colorless transparent liquid, 7.8g of oxalic acid is added, 70°C for 1h, 95g of castor oil is added to the system, reaction is carried out at 75°C for 2h, 51.3g of ethylene glycol is added, reaction is carried out at 75°C for 1h, 10.2g of concentrated sulfuric acid is added dropwise under stirring for 1h, the reaction is carried out by heat preservation for 2h, the concentrated sulfuric acid is washed out with 60mL of saturated sodium chloride solution, the pH is adjusted to 6-7, and the softener is obtained.
[0037] Example 3
[0038] A method for preparing a pallet for carrying hides in a tannery from chrome-containing leather ash, characterized in that:
[0039] (1) 10 kg of dried chrome-containing ground leather ash, 2.0 kg of special modified rubber, 0.4 kg of polyvinyl acetate, 0.06 kg of 3,4-dimethylaniline, 0.3 kg of synthetic fatliquor for pallets, and 0.15 kg of softener were mixed evenly, placed at room temperature for 30 minutes, put into a 40-50 mm mold, the pressure of the flat plate vulcanizer was 11 MPa, the temperature was 115°C, heated and pressurized in the flat plate vulcanizer, and the processing time was 55 minutes. Then, 15 g of isopropyl palmitate was sprayed on the surface of the leather ash extrudate, and the pallet carrier was obtained after curing;
[0040] (2) 5 kg of PE particles are placed in a twin-screw extruder to obtain master batches, and then the modified master batches are placed in a casting device to prepare a modified film. The twin-screw extruder and the casting device both have multiple heating zones, zone 1 is 160°C; zone 2 is 170°C; zone 3 is 165°C, the extruder speed is 40 r / min, and the casting speed is 70 r / min. The PE particles are sprayed onto the tray carrier obtained in step (1). The spraying speed is controlled so that the thickness of pE around the tray carrier is 2.0 to 2.5 cm. The tray carrier is left to stand for 1 hour to obtain a tray with a skin.
[0041] The preparation method of the special modified rubber is as follows: 50g of versatate vinyl carbonate, 60g of vinyl acetate, 1.25g of polyvinyl alcohol and 120g of deionized water are added into a flask, and the polyvinyl alcohol is fully dissolved at 75°C; then 1.3g of ammonium persulfate (dissolved in 50ml of water) is added, the dropping speed is adjusted, the dropping time is 2h, and after the dropping is completed, the temperature is kept at 75°C for 1h, and then 5g of butyl acrylate, 4.5g of hydroxyethyl acrylate, 1.5g of ammonium persulfate (dissolved in 50ml of water), 1.5g of triethoxyvinylsilane and 1g of 2-ethoxyethylamine are added, and the mixture is stirred and reacted at 80°C for 1.5h, and then 1.5g of N-phenylurea is added, and the mixture is reacted at 45°C for 30min, cooled to room temperature, and discharged to obtain the modified rubber;
[0042] The preparation method of the special synthetic fatliquor for pallets is as follows: 21 g of tetradecanol is added into a flask, heated to 75°C, and the water therein is removed by vacuuming, and then 10.4 g of maleic anhydride and 1.9 g of anhydrous sodium acetate are added under stirring, and the mixture is reacted at 88°C, and then 10.1 g of diethanolamine and 6.8 g of 2,2-dihydroxymethylpropionic acid are added, and the mixture is heated to 110°C, and 4.0 g of pentadecylsulfonyl chloride is added at the same temperature, and the mixture is reacted for 1 hour, and then 12.5 g of anhydrous sodium sulfite is added, and the mixture is stirred and reacted at 70°C for 1 hour, and finally 50 g of water is added, and the mixture is reacted at 80°C for 2 hours. The obtained product is the special synthetic fatliquor for pallets.
[0043] The preparation method of the softener is as follows: 10.3g of soluble starch and 150g of deionized water are added to a reaction bottle, the dissolved soluble starch is put into a water bath, nitrogen protection is maintained at a temperature of 15°C, 4.5g of sodium periodate is added evenly three times, oxidation is carried out in the dark for 18h, 10.9g of barium chloride is added, stirring is carried out for 30min, suction filtration is carried out to obtain a colorless transparent liquid, 7.8g of oxalic acid is added, the reaction is carried out at 70°C for 1h, 94g of castor oil is added to the system, the reaction is carried out at 70°C for 1.5h, 45.8g of ethylene glycol is added, the reaction is carried out at 70°C for 1h, 10g of concentrated sulfuric acid is added dropwise under stirring for 1h, the reaction is carried out at the temperature for 1.5h, the concentrated sulfuric acid is washed out with 60mL of saturated sodium chloride solution, the pH is adjusted to 6-7, and the softener is obtained.
[0044] The modified rubber was cast in a polytetrafluoroethylene template and dried naturally at room temperature to obtain a latex film. The latex film was balanced at a relative humidity of 55% and room temperature for 24 hours before various performance tests were performed.
[0045] Water resistance of latex film: water absorption and contact angle are used for testing. Water absorption is measured according to HG / T 21612-1985 standard, and contact angle is measured by static drop contact angle measuring instrument for measuring the contact angle of water drop (water drop diameter is 1-2mm) on acetic acid vesicle latex film.
[0046] Freeze resistance test: Place the sample in a refrigerator (-4°C) and freeze it for 2 hours. Then take it out of the refrigerator and thaw it naturally at room temperature. Observe its fluidity and use the ratio of viscosity after freezing to viscosity before freezing to measure the freeze resistance, that is, cold resistance (use a rotational viscometer to measure viscosity).
[0047] Table 1 Properties of modified rubber
[0048]
[0049]
[0050] The commercially available white latex is selected from the white latex D230 produced by Foshan Nianbilao Chemical Technology Co., Ltd.
[0051] From Table 1, it can be found that the water absorption rate and contact angle of the modified glue are lower than and higher than those of the commercial white latex, respectively, indicating that the modified glue has strong water resistance. From the table, it can be found that the glue of the present invention has good cold resistance compared with similar products on the market. The commercially available glue after freezing is 2.2 times that of the unfrozen glue, while the cold resistance of the present invention is 1.2 to 1.3 times, which is significantly lower than the commercially available variation. Therefore, the freezing resistance of the present invention is better than that of the commercially available glue. The ratio of cold resistance (after freezing to before freezing) of Example 1 without adding butyl acrylate is 1.8, while the ratio of cold resistance (after freezing to before freezing) of Example 1 without adding hydroxyethyl acrylate is 2.2.
[0052] To judge toughness by impact strength: Cut the plate into 10mm×80mm strips on a universal prototype machine, measure the width and thickness of the middle edge and the center of the end, and take the average value as the width and thickness of the sample. When selecting a pendulum, the energy consumed by the sample fracture cannot be less than 10% of the total energy of the pendulum and cannot be greater than 90% of the total energy of the pendulum. After the air strike test, place the sample on the impact tester and start the test. The unit (impact strength / kj·m -2 ), tested in accordance with GBT1843-2008 standard.
[0053] Table 2: Properties of the objects loaded on the tray in step (1)
[0054]
[0055]
[0056] The wear resistance test is carried out according to QB / T2726--2005, and the method is improved. The wear can be judged under the condition of observation times. The wear includes three levels: slight wear, medium wear and high wear, which are judged by three experienced leather engineers.
[0057] From Table 2, it can be found that the impact strength of the pallet carrier in step (1) is higher than that of the pallet carrier without N-phenylurea, synthetic fatliquor, softener, and softener but without castor oil, indicating that N-phenylurea, synthetic fatliquor, softener, and castor oil play a special role in the pallet carrier. Since no white latex is added, the leather ash cannot stick, so there is no so-called impact strength index. From the wear point of view of the present invention, the pallet carrier of the present invention has good wear resistance.
[0058] Table 3 Properties of pallets
[0059]
[0060] From Table 3, it can be found that the impact strength of the pallet load is not much different from that of the pallet, but the impact strength is greater than that of the pallet without adding N-phenylurea, without adding pallet-specific synthetic fatliquor, without adding softener and without adding castor oil. Since the surface of the pallet is treated with plastic, the wear resistance of the plastic itself is better, so no wear test was performed.
[0061] The length and width of the leather-bearing pallet of Example 1 of the present invention are 1.2m and 0.8m respectively. 80 sheets (each with a standard weight of 25kg, a total of 2 tons) are placed on it. After 24 hours of observation, the pallet is not damaged, indicating that the pallet can withstand a leather weight of 2 tons. However, the pallets without N-phenylurea, synthetic fatliquor for pallets, softener, and castor oil are damaged in less than 8 hours. Since the surface of the pallet is treated with plastic, the waterproofness is greatly increased. Generally speaking, the raw leather has more water, while the leather blank and batch leather have less water. Therefore, this experiment did not study the low moisture content mentioned above, but theoretically there should be no problem. It shows that the pallet has no damage to the bottom leather surface, scratches, etc.
Claims
1. A method for preparing a pallet for carrying leather in a tannery using chrome-containing leather ash, characterized in that: (1) Mix the dried chrome-containing leather ash, special modified rubber, toughening agent, toughening synergist, synthetic fatliquor for pallets, and softener evenly, put them into a mold, heat and pressurize them in a vulcanizer, then spray isopropyl palmitate on the surface, and obtain a pallet carrier after curing; (2) PE particles are placed in a twin-screw extruder to obtain master batches, and then the modified master batches are placed in a casting device to prepare a modified film. The twin-screw extruder and the casting device are provided with three heating zones, zone 1 is 160° C.; zone 2 is 170° C.; zone 3 is 165° C., the speed of the extruder is 40 r / min, the speed of the casting device is 70 r / min, and the film is sprayed onto a tray carrier; The preparation method of the special modified rubber is as follows: 50g of tert-butyl carbonate, 60g of vinyl acetate, 1.1-1.4g of polyvinyl alcohol and 120g of deionized water are added into a flask, and the polyvinyl alcohol is fully dissolved at 70-80°C; 1.2-1.4g of ammonium persulfate is added, and the dropping speed is adjusted, and the dropping time is 2h. After the dropping is completed, the temperature is kept at 70-80°C for 1h, and 4-6g of butyl acrylate, 3-6g of hydroxyethyl acrylate, 1-2g of ammonium persulfate, 1-2g of triethoxyvinylsilane (vinyltriethoxysilane) and 0.5-1.5g of 2-ethoxyethylamine are added, and the mixture is stirred and reacted at 80°C for 1-2h, and 0.8-2.2g of N-phenylurea is added, and the mixture is reacted at 40-50°C for 30min, cooled to room temperature, and discharged to obtain the modified rubber; The preparation method of the special synthetic fatliquor for pallets is as follows: 21 g of tetradecanol is added into a flask, heated to 70-80° C., and the water therein is removed by vacuuming, and then 9.8-11 g of maleic anhydride and 1.6-2.2 g of anhydrous sodium acetate are added under stirring, and the mixture is reacted at 80-95° C., and then 9.6-10.6 g of diethanolamine and 6.2-7.5 g of 2,2-dihydroxymethylpropionic acid are added, and the mixture is heated to 90-130° C., and 3.2-4.8 g of pentadecylsulfonyl chloride is added at the same temperature, and the reaction time is 1 h, and then 12.5 g of anhydrous sodium sulfite is added, and the reaction time is 1 h after stirring at 70° C., and finally 45-55 g of water is added, and the mixture is reacted at 80° C. for 2 h, and the obtained product is the special synthetic fatliquor for pallets; The preparation method of the softener is as follows: 10.3g of soluble starch and 100-200g of deionized water are added to a reaction bottle, the dissolved soluble starch is put into a water bath, nitrogen protection is used, the temperature is maintained at 10-20°C, 3.8-5.3g of sodium periodate is added three times on average, oxidation is carried out in the dark for 12-24h, 10.9g of barium chloride is added, stirring is carried out for 30min, suction filtration is carried out to obtain a colorless transparent liquid, 7.8g of oxalic acid is added, the reaction is carried out at 70°C for 1h, 93-95g of castor oil is added to the system, the reaction is carried out at 65-75°C for 1-2h, 40.3-51.3g of ethylene glycol is added, the reaction is carried out at 60-75°C for 1h, 9.8-10.2g of concentrated sulfuric acid is added dropwise under stirring for 1h, the reaction is carried out by heat preservation for 1-2h, the concentrated sulfuric acid is washed out with 60mL of saturated sodium chloride solution, the pH is adjusted to 6-7, and the softener is obtained.
2. The method for preparing a tannery leather pallet using chrome-containing leather scraps as claimed in claim 1, characterized in that: (1) 10 kg of dried chrome-containing ground leather ash, 1.5-2.5 kg of special modified rubber, 0.3-0.5 kg of toughening agent, 0.04-0.08 kg of toughening synergist, 0.2-0.4 kg of synthetic fatliquor for pallets, and 0.1-0.2 kg of softener are mixed evenly, placed at room temperature for 30 minutes, put into a 40-50 mm mold, the pressure of the flat plate vulcanizer is 10-12 MPa, the temperature is 110-120° C., heated and pressurized in the flat plate vulcanizer, the processing time is 30-80 minutes, and then 10-20 g of isopropyl palmitate is sprayed on the surface of the leather ash extrudate, and the pallet carrier is obtained after curing; (2) 5 kg of PE particles are placed in a twin-screw extruder to obtain master batches, and then the modified master batches are placed in a casting device to prepare a modified film. The twin-screw extruder and the casting device have three heating zones, zone 1 is 160° C.; zone 2 is 170° C.; zone 3 is 165° C. The speed of the extruder is 40 r / min, and the speed of the casting device is 70 r / min. The PE particles are sprayed onto the tray support obtained in step (1). The spraying speed is controlled so that the thickness of pE around the tray support is 2.0-2.5 cm. The tray is left to stand for 1 hour to obtain a tray with a skin.
3. The method for preparing a tannery load-bearing leather pallet using chrome leather ash as claimed in claim 1 or 2, wherein the toughening agent is any one of nitrile rubber, polyvinyl butyral and polyvinyl acetate.
4. The method for preparing a tannery load-bearing leather pallet using chrome leather ash as claimed in claim 1 or 2, wherein the toughening synergist is any one of sodium p-styrene sulfonate, cycloisopropyl malonate and 3,4-dimethylaniline.
Citation Information
Patent Citations
Method for manufacturing particle board by using chromium-containing leather-grinding ash
CN110527305A